A comparative study on urban environment and their contribution to the effect of Urban Heat Island (Putrajaya vs Shah Alam) / Nursyuhaida Jail - Jail, Nursyuhaida (Faculty of Architecture, Planning and Surveying, 2015)
Urban Heat Island are common phenomenon in Malaysia. This phenomenon has been happen since a few decades in Malaysia. The phenomenon is given the “island” designation because the isotherm patterns of near-surface air temperature resemble the contours of an island in the “sea” of the surrounding cooler rural areas. The growth of city, the increases of population in the city and the decreases of green areas are the causes of urban Heat Island phenomenon. The development in the city is grow fast to fulfill the needed of the population in the city to continuous their live in the city. This dissertation is aimed on the comparative study on urban environment and their contribution to the effect of Urban Heat Island between Putrajaya and Shah Alam. The objectives of this study is to investigate the effect of Urban Heat Island, to identify the design and surface material uses on urban building, to compare the surrounding air temperature between Putrajaya and Shah Alam and to find the solution to reduce the effect of Urban Heat Island to the environments. From the study, find that the sensitive population such older adults and those with existing health condition are affected with the effect of Urban Heat Island. Besides, the urban design that are mostly used in urban building environment is quadrilateral shape design, medium rise building and surface material of concrete. This are contribute to the Urban Heat Island by trapping the thermal heat and reflected heat to the surrounding. Based on the result, the environment in Putrajaya is more contribute to the effect of Urban Heat Island compare to Shah Alam. The intensive solution to come out to reduce Urban Heat Island effect and give comfort to the people in the city.